Dysfonctions mécaniques dans les interstices de l’infrastructure - Paul Fabié; Joaquin Ruiz Zubizarreta (EchoGéo)
This ethnographic essay proposes a reflection on machines from the interstitial geographical situations in which two Guarani peoples on either side of the Paraguay-Brazil border are reduced. In this territory governed by the agribusiness infrastructure, machines are a daily feature of indigenous reality. Some are dysfunctional and became landscape; some accelerate native life; others make work easier or blur the lines between the imaginary worlds of tradition and modernity, mechanics and animals, development and resistance. This brings out the fertility and inventiveness of mechanical uses and conceptualizations.